Implementation Marketing Mix Strategy in the New Frozen Food Business: Nugget Duck-Duckan - Riskung Karim Marsuki; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2019)
The frozen food business is one of the most desirable businesses and has a good prospect. There have been many businesses that have made a huge profit from the frozen food business. This is evidenced by the increasing number of frozen food businesses that stand from day to days with a product offering each of them. But there are also frozen food businesses that go to a bankrupt due to the marketing strategies does not right and the quality of service is less than optimal. It means that the success of a frozen food business in winning competition is determined by the application of an appropriate marketing strategy. The strategy of maturity to support competitive advantage products that have a competitors. Basically, almost for all successful businesses they are really understand the 4P concept (Product, Place, Price, Promotion) marketing mix, how to run, where a business will go, and who should be involved. The implementing a marketing strategy begins by analyzing the overall situation of the company. Marketers must conduct a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in company as a whole seller. Besides SWOT, Segmenting, Targeting Positioning is also needed to classify the market that will be targeted. Here, SWOT analysis can be used to understand a company business mechanism to be a better condition also competitive for company strength and deter threats